Development of an Evaluation Method to Measure the Accuracy of Inpatient Diagnosis Codes at Lawang Regional Hospital - Diva Nur Asmianova; Achmad Jaelani Rusdi; Rizka Andika Sari (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: The provision of diagnosis codes on medical record documents needs to be carried out accurately based on the ICD-10 book. The role of medical personnel and coding officers affects the accuracy of the diagnosis code. The coding officer must ensure that the medical record data is clear and complete such as severe or critical conditions, spesific anatomical positions, the course of health disorders, complications or the patient’s history to support the primary diagnosis. Objectives: The research objevtives to be achieved in this study evaluate and examine several causes that affect the accuracy of the selection of patient diagnosis codes at Lawang Hospital. Research Metodes: The type of research implemented is descriptive with a quantitative approach. Data collection is taken by observation, interviews, and code accuracy checklist. The population used in this study is all medical record files of inpatients in May with a total of 645 medical record documents. The sample was taken using a simple random sampling technique with as many as 25 medical record files of inpatients. Data analysis was carried out by univariate analysis by looking at the percentage of each research variable. Results: This study shows that the level of code accuracy is still said to be low because it still reaches 84% with as many as 21 documents and the code inaccuracy reaches 16% with as many as 4 documents. . Conclusion: The cause of inaccuracy will be due to the completeness of the primary and secondary diagnoses that are less specific, lack of communications between officers regarding clarity in writing in medical record documents, and some diagnoses do not include the 4th character in the case of fracture, namely the close or open description. For the development of evaluation, officers can take part in codification training and make help books such as pocket books that contain a collection of diagnosis codes. Keywords: Accuracy; Diagnosis Code; Medical Record; Hospital